Fluorescence microscopic visualization and quantification of initial bacterial colonization on enamel in situ - Hannig, C.; Hannig, M.; Rehmer, O.; Braun, G.; Hellwig, E.; Al-Ahmad, A. (Archives of oral biology, 2007)
The acquired salivary pellicle has been defined as proteinaceous film free of bacteria. However, due to the large numbers of microorganisms existent in the oral fluids, it is conceivable that adherent bacteria are already present in the initial pellicle. The aim of this in situ study was to visualize and to quantify these bacteria. Initial biofilm formation was performed on bovine enamel slabs mounted buccally on individual splints and carried in situ by six subjects for 3, 30 and 120 min, respectively. After intraoral exposure, the slabs were rinsed with saline solution and the adherent bacteria were investigated with the following fluorescence microscopic methods: staining with 4′,6-diamidino-2-phenylindole (DAPI), staining of vital and nonvital bacteria with fluoresceinediacetate and ethidiumbromide (live/dead staining) and fluorescence in situ hybridization (FISH) of eubacteria and streptococci, respectively. In addition, determination of colony forming units after ultrasonically induced detachment of bacteria was performed. With all the methods, bacteria were detected in the initial in situ biofilm irrespective of the formation time. The numbers of bacteria revealed high intraindividual and interindividual variability and the microorganisms were distributed randomly in small aggregates. The results of the epifluorescence microscopic techniques corresponded well. The mean number of adherent bacteria detected was in the range of 10–20 × 10 4 cm −2. Already after 3 min, adherent bacteria are present in the initial pellicle. For the first time, DAPI-staining as well as FISH have proven success for visualization of initial intraoral colonization of enamel specimens.